2001
DOI: 10.1161/hc4001.097036
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcome After Off-Pump Versus On-Pump Coronary Bypass Surgery

Abstract: Background-The use of cardiopulmonary bypass during coronary artery bypass surgery (CABG) has been associated with substantial morbidity. The recent introduction of cardiac stabilizers facilitates CABG without cardiopulmonary bypass (off-pump CABG), but it is unknown whether cardiac outcome after off-pump surgery is similar to that for the on-pump procedure. Methods and Results-In a multicenter trial, 281 patients (mean age 61 years, SD 9 years) were randomly assigned to off-pump or on-pump CABG. In-hospital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
113
4
10

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 468 publications
(136 citation statements)
references
References 32 publications
9
113
4
10
Order By: Relevance
“…10,15 Moreover, the consistency of association between HSP65 antibodies and postoperative AF in both the overall and subgroup analyses validates our conclusion regardless of the operative technique used.…”
Section: Mandal Et Al Hsp60 Antibodies and Atrial Fibrillation 2589supporting
confidence: 82%
“…10,15 Moreover, the consistency of association between HSP65 antibodies and postoperative AF in both the overall and subgroup analyses validates our conclusion regardless of the operative technique used.…”
Section: Mandal Et Al Hsp60 Antibodies and Atrial Fibrillation 2589supporting
confidence: 82%
“…[5][6][7] Several large, nonrandomized, retrospective case series comparing CABG surgery performed on the beating heart (off pump) and conventional CABG surgery performed with CPB (on pump) have indicated an advantage to CABG surgery without CPB; however, selection bias toward lower-risk cases in CABG without CPB remains an issue. 8 -14 The largest randomized studies published to date are conflicting, with some demonstrating decreased length of hospitalization and myocardial enzyme release, 15 whereas others demonstrate decreased incidence of atrial fibrillation, length of hospitalization, and blood-product utilization with CABG surgery performed on the beating heart. 16,17 The most recent trial demonstrated decreased blood-product requirement, myocardial enzyme release, and length of hospitalization in beating-heart surgery patients.…”
Section: See P 810mentioning
confidence: 99%
“…Additionally, the duration of the ICU stay for patients submitted to the surgery without ECC was significantly shorter than for patients that underwent the surgery with ECC, similarly to that observed by another study 11 . Other results, concerning the cost analysis, did not show a decrease in the ICU stay for patients without ECC; however, all of them showed a shorter intubation time [16][17][18] .…”
Section: Discussionmentioning
confidence: 86%
“…The importance of the patients' extubation time in the mentioned studies 17,19 received a higher clinical attention, rather than an economical one. Furthermore, these authors did not consider, for the economic analysis, the ICU stay duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation